Chinese senior high school EFL students' metacognitive awareness and reading-strategy use - Zhang, Lawrence Jun; Wu, Aijiao (Reading in a foreign language, 2009)
This paper reports findings from a study that assesses metacognitive awareness and reading-strategy use of Chinese senior high school students who are learning English as a foreign language (EFL). A total of 270 students responded to a 28-item survey of reading strategies (SORS). The strategies were classified into 3 categories: global, problem-solving, and support. The results showed that the students reported using the 3 categories of strategies at a high-frequency level. Both the main effect for strategies and the main effect for learners' proficiency were significant. The high-proficiency group outperformed the intermediate group and the low-proficiency group in 2 categories of reading strategies: global and problem-solving; but no statistically significant difference was found among the 3 proficiency groups in using support strategies. Pedagogical implications of these findings are discussed in relation to the changing Chinese society.